Determining groundwater availability and aquifer recharge using GIS in a highly urbanized watershed - Conicelli, Bruno (2020)
Extensive urbanized areas, characterized by waterproofed soils, increase runoff, which reduces the rainwater infiltration into the ground. However, water, sewer, and rainwater distribution systems leak, as there is excess irrigation in green areas, resulting in anthropic recharging in urban aquifers larger than in rural areas with equivalent climates. This scenario occurs in the Upper Tietê Watershed (UTW), an area of 5,868 km² that drains the principal rivers of the São Paulo's metropolitan region in Brazil, where groundwater plays a complementary role for domestic, industrial, and agricultural supplies, totalizing extraction rates higher than 11 m³/s. In this paper, a Geographical Information System (GIS) was established to assess regional groundwater availabilities using adaptations of classic recharge methods such as soil water budget calculations and estimation of minimum sustainable river flow. For this, a surface runoff map, based on soil and slope terrain data, was evaluated using the information on water and sanitation infrastructure and meteorological data. We found that recharge in urban areas (with water and sewer mains) was 437 mm/yr and 106–407 mm/yr in rural areas. Considering the need to maintain a minimum historical flow of 20 m³/s in the hydrographic basin of the Tietê River, the total exploitable groundwater is 33 m³/s. The compilation of various GIS methods can help decision-makers develop alternative water security management plans in complex urbanized-regions such as in the metropolis of São Paulo.